ANALISIS PROSES PENGAMBILAN KEPUTUSAN PEMBERIAN KREDIT PEMILIKAN RUMAH MENGGUNAKAN MODEL HERBERT A. SIMON DALAM MENERAPKAN METODE ANALYTICAL HIERARCHY PROCESS - Desfa, Riega Gita Prista; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2023)
House ownership credit is a government program provided by banks for the people. In the process, there are requirements that must be fulfilled by prospective clients before they get the loan. The requirements are used by the banks as the early assessment so that they can avoid non-performing loan. In making their decisions, whether to approve a loan or not, banks apply the Five Cs as the cautiousness principle in assessing their prospective clients. The objective of this research is to identify decision-making processes that is analyzed using he Herbert A. Simon model and Analytical Hierarchy Process. The Simon model consists of phases; they are intelligence, design, choice, and implementation. Meanwhile, the decision-making process applied by PT Bank Tabungan Negara branch of Madiun did not include the choice phase, which increase the probability of non-performing loan. The Analytical Hierarchy Process is applied to help in credit decision-making using the highest weight, and the applicable criteria is the Five Cs. This method provides assessment on paired comparisons with questionnaires given to the decision makers. This study finds that criterion with the highest weight is character (0.495739012), followed by capital (0.248389672), capacity (0.14426402), collateral (0.066977249), and condition (0.044630047). Therefore, the bank should consider character more in their decision.